Various Methods of Evapotranspiration - Prof. Chapala Bahidar, Prof. Sagar Chandra Senapati, Prof. Bijoy Kumar Sahu (International Journal of Modern Agriculture, 2020)
Evapotranspiration (ET) is a process by which water us transferred from the land to the atmosphere by evaporation from the soil and other surfaces and by transpiration from plants. It is an important process in the water cycle because it is responsible for 15% of the atmosphere’s water vapor. Without that input of water vapor, clouds couldn’t form and precipitation would never fail. In simulating the hydrological effect of climate change, evapotranspiration plays a central role and the study of the predicted evapotranspiration methods in hydrological models is important. It is a significant factor for the management of agriculture and water. The methods of evaluation have significant regional differences. The Food and Agriculture Organization (FAO) recommended Penman – Monteith (P‐M) method that is widely accepted, but requires a high degree of data. Various methods were employed in order to estimate the range of temperature, radiation and physical methods. Therefore, the PET values of all the above listed methods have been estimated for the study area. This paper synthesizes and classifies the evapotranspiration evaluation methods which have been used in the hydrological models into the integrated conversion methods and classifies the methods by their mechanism.